Simultaneous treatment for anal fissure and hemorrhoids - J.P. Feleshtynsky; A.J. Noyes (Group of Companies Med Expert, LLC, Kyev, Ukraine, 2023)
When using surgical approach to treatment for combined anal fissure and hemorrhoids doctor always faces the question of whether to divide the procedure into two sequential stages or to perform a simultaneous surgical intervention, and in which cases one or the other should be done. Purpose - to improve the results of treatment for patients with anal fissure in combination with chronic hemorrhoids by combining fissurectomy with transanal hemorrhoidal dearterialization (THD). Materials and methods. 177 patients with combination of anal fissure and hemorrhoids were studied. The Group I (GI) - fissure excision and hemorrhoidectomy, 60 patients. The Group II (GII) - anal fissure excision without surgery for hemorrhoids, 60 patients. The Group III (GIII) - proposed method used, 57 patients. Laser Doppler flowmetry was performed to assess blood flow intensity in fissure area. The assessment of treatment outcomes in patients was based on the following criteria: pain intensity, urinary retention in early postoperative period, postoperative wound suppuration, disease recurrence, iatrogenic incontinence, duration of postoperative hospital stay. Qualitative parameters are presented as the absolute number of cases (n) and their percentage (%). Comparison of these parameters between groups was performed using the Pearson's χ2 test and the Fisher's exact test. Statistical analysis was conducted by STATA 12.1 statistical package. Results. Pain intensity: GI - 8±1, GII - 6±2, GIII - 4±1. Urinary retention: GI - 19 (31.6%), GII - 8 (13%), GIII - 6 (10.5%). Wound suppuration: GI - 5 (8.3%), GII - 1 (1.7%), GIII - 1 (1.7%). Hospital stay (days): GI - 6±1.2, GII - 4±1.3, GIII - 3±1.1. Fissure recurrences: GI - 5 (8.3%), GII - 2 (3.3%), GIII - 1 (1.7%). Hemorrhoid recurrence: GI - 6 (10%), GIII - 2 (3.5%). Iatrogenic incontinence: GI - 4 (6.7%), GII - 1 (1.7%), GIII - 0. Significant decrease in relative risk of complications (by 88%) in GIII compared with GI - OR=0.12 (0.04-0.29), p=0.0001, and a tendency to reduction of complication risk by 15% compared with GII - OR=0.85 (0.29-2.4), p=0.734 was observed. Blood flow intensity (flowmetry results) in GII and GIII was comparable. Conclusions. Simultaneous anal fissure excision and THD can improve treatment outcomes. This method does not impair blood flow in the area of anal fissure. Proposed method is both radical and minimally invasive. The research was carried out in accordance with the principles of the Helsinki Declaration. The study protocol was approved by the Local Ethics Committee of all participating institutions. The informed consent of the patient was obtained for conducting the studies. No conflict of interests was declared by the authors.